Cyclotetrabenzil-Based Porous Organic Polymers with High Carbon Dioxide Affinity - Ashirov, Timur; Alrayyani, Maymounah; Song, Kyung-Seob; Miljanić, Ognjen Š.; Coskun, Ali (Organic Materials, 2021)
Porous organic polymers (POPs) incorporating macrocyclic units have been investigated in recent years in an effort to transfer macrocycles' intrinsic host–guest properties onto the porous networks to achieve complex separations. In this regard, highly interesting building blocks are presented by the family of cyclotetrabenzoin macrocycles with rigid, well-defined, electron-deficient cavities. This macrocycle shows high affinity towards linear guest molecules such as carbon dioxide, thus offering an ideal building block for the synthesis of CO2-philic POPs. Herein, we report the synthesis of a POP through the condensation reaction between cyclotetrabenzil and 1,2,4,5-tetraaminobenzene under ionothermal conditions using the eutectic zinc chloride/sodium chloride/potassium chloride salt mixture at 250 °C. Notably, following the condensation reaction, the macrocycle favors three-dimensional (3D) growth rather than a two-dimensional one while retaining the cavity. The resulting polymer, named 3D-mPOP, showed a highly microporous structure with a BET surface area of 1142 m2 g−1 and a high carbon dioxide affinity with a binding enthalpy of 39 kJ mol−1. Moreover, 3D-mPOP showed very high selectivity for carbon dioxide in carbon dioxide/methane and carbon dioxide/nitrogen mixtures.
Keywords: macrocycles; porous polymers; host–guest chemistry; ionothermal synthesis; CO2 capture